BIBLE INSPIRATION IN WOLFHART PANNENBERG’ THEOLOGY: AN EXAMINATION - Legi, Glenny W; Pasuhuk, Suryanica Aristas (Klabat Theological Review, 2022)
Wolfhart Pannenberg was a theologian from German. He was a Lutheran theologian. His concept of revelation and inspiration was widely debated among Protestant and Catholic theologians. This article attempts to examine Wolfhart Pannenberg’s theology of Biblical Inspiration. A biblical examination of the inspirations in Pannenberg’s theology shows contrasting things. His idea of revelation is not direct communication between the Divine and man but rather as history, contrary to the biblical notion. Pannenberg rejected Divine intervention in biblical inspiration. This led him to focus on the role of man in Inspiration. For him, the authors played an active role, in cognitive processes. According to the Bible, writers have a passive role, because they are led and directed by the Holy Spirit. Therefore, Pannenberg's idea of the Bible as a human document is not in harmony with the teachings of the Bible Key words: revelation, inspiration, biblical. Bibliography Bloesch, Donald G. Holy Scripture: Revelation, Inspiration and Interpretation. Downers Grove, IL: IVP Academic, 2005. Canale, Fernando L. “Revelation and Inspiration: The Classical Model.” Andrews University Seminary Studies 32 (1994): 22-30. ________. “Revelation and Inspiration,” Understanding Scripture: An Adventist Approach, ed., by, George W. Reid. Hagerstown, MD: Review & Herald, 2005. Carson, D. A. and Douglass J. Moo. An Introduction to the New Testament. Grand Rapids, MI: Zondervan, 2009. Dederen, Raoul. “Revelation-Inspiration Phenomenon According to the Bible Writers,” in, Adventist Theological Society Occasional Papers, ed., by, Frank Holbrook dan Leo Van Dolson. Berrien Springs, MI: Adventist Theological Society Publications, 1992. Grudem, Wayne. Systematic Theology: Introduction to Biblical Doctrines. Downers Grove, IL: IVP Academic, 2004. Gulley, Norman R. Systematic Theology I: Prolegomena. Berrien Springs, MI: Andrews University Press, 2003. Hagner, Donald A. The New Testament: Historical and Theological Introduction. Grand Rapids, MI: Baker Academic, 2013. Hasel, Frank M. “The Scripture in the Theologies of W. Pannenberg and D. G. Bloesch: An Investigation and Assessment of Its Origin, Nature and Use.” (Ph.D Dissertation, Andrews University, 1994. McKenzie, David. Wolfhart Pannenberg and Religious Philosophy. Lanham, MD: University of America, 1980). Ministerial Association of General Conference of SDA, Seventh-day Adventist Believe: A Biblical Exposition of 28 Fundamental Doctrines. Nampa, ID: Pacific Press, 2005. Pannenberg, Wolfhart. Systematic Theology, 3 vols., trans., by, Geoffrey Bromiley. London: T & T Clark International, 2004. ________. Introduction to Systematic Theology. Grand Rapids, MI: Eerdmans, 1991. ________. Revelation as History. New York: The Macmillan Company, 1968. ________. What is Man?: Contemporary Anthropology in Theological Perspective. Philadelphia: Fortress Press, 1970. White, Ellen G. Steps to Christ. Washington, DC: Review & Herald, 1915.